Educação empreendedora no ensino técnico: experiências, percepções e práticas educacionais - Silva, Simão Pedro Santos da (2024)
Problematization: Entrepreneurial education has stood out as an essential educational approach to prepare students for the challenges of the job market. The perceptions, experiences and opinions of students and teachers about Entrepreneurial Education in Technical Education contribute to a better understanding of interest in entrepreneurship, quality of entrepreneurial education, future aspirations and challenges. Research Question: How does entrepreneurial education contribute to the development of entrepreneurial skills in technical education students? Objectives: The objective of this research is to analyze how entrepreneurial education contributes to the development of entrepreneurial skills in technical education students, through a program in a technical education institution. Methodology: The research follows a qualitative, descriptive and exploratory approach, with data collection carried out through a semi-structured interview with the school director and two focus groups composed of six teachers and five students from a technical education institution. The scripts used in the interviews and focus groups were prepared based on a literature review, ensuring theoretical alignment. The information obtained was organized and coded with the help of software specialized in qualitative analysis and subjected to content analysis to explore the effects of entrepreneurial teaching on participants. Data processing: The collected data was transcribed and categorized using the Atlas TI software and analyzed using the content analysis approach, aiming to identify relevant themes, patterns and perceptions. Main Results: The research highlighted the challenges of... implementing entrepreneurial education in technical education, the importance of methodologies that integrate entrepreneurship practices to promote significant changes in the training of students, developing an innovative and adaptable professional profile, in addition to development of important skills, such as Implementation of Entrepreneurial Education, Innovative Strategies and Practices, Entrepreneurial Skills from the perspective of the director, teachers and students, Resistances and Challenges and External partnerships. Relevance: This study strengthens the field of research in Entrepreneurial Education in Technical Education, stimulating a deeper discussion on the topic. It also contributes to the academic evolution of the area by offering subsidies for the implementation of educational policies that prepare more capable entrepreneurs for market challenges, aligning their projects with the eradication of poverty (SDG 1) and the improvement of education (SDG 4).